Real and Nominal Interest Rates under Uncertainty: The Fisher Theorem and the Term Structure - Benninga, Simon; Protopapadakis, Aris (Journal of Political Economy, 1983)
This paper examines the relation between nominal and real interest rates, and the nominal and real term structure under uncertainty. We show that two separate risk terms cause the Fisher theorem to fail. One risk term is related only to the variability of money prices, while the other is related to the purchasing power riskiness of the nominal bond. Monetary policy can affect the value of both these risk terms. We also show that the pure expectations hypothesis of the term structure fails for both real and nominal bonds because of risk premia. Even if the economy is neutral with respect to monetary policy, monetary policy can alter the nominal term structure.